Identification of Psychosocial and Sociodemographic Factors Associated with Low Medication Awareness in COPD Subjects: A Cross-Sectional Study, Findings from the Indonesian Family Life Survey 5 - Jannah W; Alfian SD; Abdulah R (International Journal of COPD)
Wardatul Jannah,1– 3 Sofa D Alfian,1,2 Rizky Abdulah1,2 1Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Jatinangor, Indonesia; 2Drug Utilization and Pharmacoepidemiology Research Group, Center of Excellence for Pharmaceutical Care Innovation, Universitas Padjadjaran, Jatinangor, Indonesia; 3Doctoral Program of Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Jatinangor, IndonesiaCorrespondence: Sofa D Alfian, Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Jl. Raya Jatinangor, KM 21, Jatinangor, Sumedang, Indonesia, Tel/Fax +62-022-7796200, Email sofa.alfian@unpad.ac.idPurpose: To identify psychosocial and sociodemographic factors influencing low medication awareness among patients with Chronic obstructive pulmonary disease (COPD) based on Indonesian Family Life Survey 5 (IFLS-5).Methods: This study used a cross-sectional design, with data from IFLS-5 (2014/2015). Inclusion criteria were subjects with a self-reported diagnosis of COPD and aged at least 15 years. Two main factors were identified as modifiable psychosocial factors (eg, insomnia, depressive symptoms, happiness status, general health check status, smoking status, and health service satisfaction) and as non-modifiable sociodemographic factors (eg, gender, age, education level, marital status, economic status, insurance ownership, religiosity, comorbidity, and place of residence). Multivariate logistic regression analysis was used to explore the relationship between these factors and the awareness of COPD medication, by observing the adjusted odds ratio (aOR) within a 95% Confidence Interval.Results: There were 618 subjects identified with COPD, of which 53.40% were male. 84.30% of subjects have low medication awareness. Non-modifiable sociodemographic factors such as age 15– 25 years (aOR: 2.531; 95% CI 1.024– 6.253; p-value 0.044), age 26– 35 years (aOR: 3.418; 95% CI 1.444– 8.091; p-value 0.005), high school education level (aOR: 4.870; 95% CI 1.685– 14.078; p-value 0.003), and modifiable psychosocial factors such as satisfaction with health services with the category “sufficient” (aOR: 2.510; 95% CI 510; 95% CI 1.508– 4.176; p-value 0.000), and subjects who smoked (aOR: 1.894; 95% CI 1.147– 3.127; p-value 0.013), were significantly associated with low COPD medication awareness.Conclusion: This study shows that most subjects with COPD had low medication awareness, which is influenced by factors such as age, education level, smoking habits, and satisfaction with health services. This highlights the need for targeted interventions for high-risk groups. Limitations of this study include reliance on self-reported data, which may lead to recall bias. In addition, this study was unable to provide evidence of a causal relationship.Keywords: COPD, medication awareness, medication adherence, IFLS-5